Children under institutional care and in foster homes, 1933 : dependent and neglected children under the care of public and private institutions or agencies, not including juvenile delinquents / U.S. Department of Commerce, Bureau of the Census, prepared under the supervision of Dr. Leon E. Truesdell, Chief Statistician for Population. (1935)
Summary goes here